Molecular phylogenetics of snailfishes (Cottoidei: Liparidae) based on MtDNA and RADseq genomic analyses, with comments on selected morphological characters - Orr, James Wilder; Spies, Ingrid; Stevenson, Duane E.; Longo, Gary C.; Kai, Yoshiaki; Ghods, Sam; Hollowed, Myles (Zootaxa, 2019)
Phylogenetic relationships of snailfishes of the family Liparidae were analyzed on the basis of two sets of molecular sequence data: one from the mitochondrial DNA cytochrome c oxidase subunit one gene (COI) and another from restriction-site associated genome-wide sequences (RADseq). The analysis of COI sequence data from at least 122 species of 18 genera from the Pacific, Atlantic, and Southern oceans resulted in a moderately well-resolved phylogeny among the major clades, albeit with significant polytomy among central clades. Nectoliparis was the sister of all other members of the family, followed by Liparis. Liparis, Careproctus, and Paraliparis were paraphyletic. Liparis was recovered in two closely related clades, with L. fucensis sister of all other liparids except Nectoliparis, and both Careproctus and Paraliparis were each recovered among at least three widely separated clades. The RADseq analysis of 26 species of 11 genera from the eastern North Pacific strongly confirmed the overall results of the COI analysis, with the exception of the paraphyly of Liparis due to the absence of L. fucensis. Our results show that the pelvic disc has been independently lost multiple times and the pectoral-fin girdle has been independently reduced in multiple lineages.